2020
DOI: 10.3390/genes11010115
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis and Substitution Rate Estimation of Colonial Volvocine Algae Based on Mitochondrial Genomes

Abstract: We sequenced the mitochondrial genome of six colonial volvocine algae, namely: Pandorina morum, Pandorina colemaniae, Volvulina compacta, Colemanosphaera angeleri, Colemanosphaera charkowiensi, and Yamagishiella unicocca. Previous studies have typically reconstructed the phylogenetic relationship between colonial volvocine algae based on chloroplast or nuclear genes. Here, we explore the validity of phylogenetic analysis based on mitochondrial protein-coding genes. We found phylogenetic incongruence of the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…The different substitution rates may be associated with the nature and accuracy of organelle-targeted DNA maintenance machineries (Sloan & Taylor, 2012). Furthermore, phylogenetic incongruence was observed between seven genes (rpl2, atpF, atpI, ccsA, cemA, chlB, and psbB) and four genes (atpB, psaB, rpl5, and ycf4) or others, which could be owing to systematic error, stochastic error, and biological factors (Hu et al, 2020). The variable sites, substitution rate (Ka/Ks), and gene evolution rate did not significantly differ between genes that supported Topology I and Topology II.…”
Section: Discussionmentioning
confidence: 99%
“…The different substitution rates may be associated with the nature and accuracy of organelle-targeted DNA maintenance machineries (Sloan & Taylor, 2012). Furthermore, phylogenetic incongruence was observed between seven genes (rpl2, atpF, atpI, ccsA, cemA, chlB, and psbB) and four genes (atpB, psaB, rpl5, and ycf4) or others, which could be owing to systematic error, stochastic error, and biological factors (Hu et al, 2020). The variable sites, substitution rate (Ka/Ks), and gene evolution rate did not significantly differ between genes that supported Topology I and Topology II.…”
Section: Discussionmentioning
confidence: 99%
“…The higher substitution rate observed in mitochondrial protein-coding genes is the result of the high mutation rate caused by the presence of oxygen free radicals in mitochondria [ 51 ]. Previous studies have also found that the substitution rates of mitochondrial genes in green algae Volvulina compacta and the red algal genus Porphyra are greater than those of chloroplast genes [ 52 , 53 ]. By contrast, the opposite result is observed in most seed plants, in which the mitochondrial substitution rate is estimated to be lower than that of the chloroplast [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…The model was run with the following settings in the codeml.ctl files: runmode = − 2 and CodonFreq = 2. To ensure the accuracy and reliability of the data, synonymous substitution values > 5 were discarded from the subsequent analysis [41]. Bar plots and scatter plots of the values of dN, dS and dN/dS were generated for comparing mutation rates and screening of the selected genes.…”
Section: Substitution Rate Estimationmentioning
confidence: 99%